Economic Performance and Production Efficiency of Red Chili Farming within an Agropolitan Agricultural System - Bachrul, Nur Alam (Edupedia Publisher, 2025)
Sustainable agricultural development requires farm-level efficiency to be analyzed within integrated regional systems. Despite the economic importance of red chili farming, empirical evidence linking production efficiency and economic performance within agropolitan agricultural systems remains limited. This study applied a quantitative explanatory approach to assess the economic performance and production efficiency of red chili farming within an agropolitan system. Farm income analysis was used to evaluate economic viability, while a Cobb–Douglas production function estimated input elasticities and returns to scale based on primary survey data from red chili farmers. The results indicate that red chili farming is economically viable, generating a net farm income of IDR 4,597,870.97 per production cycle on 2,080 m² of land, with revenue–cost ratios of 2.59 (cash costs) and 1.59 (total costs). Average productivity reached 0.44 kg per plant, reflecting moderate performance constrained by inefficient input allocation. The production function analysis reveals increasing returns to scale, with a total elasticity of 1.28533. The study demonstrates that efficiency and favorable scale dynamics underpin the economic sustainability of red chili farming within agropolitan systems. These findings highlight the role of efficiency-oriented interventions and system-level coordination in supporting integrated and sustainable horticultural development.